International day for the evaluation of abdominal obesity (IDEA): A study of waist circumference, cardiovascular disease, and diabetes mellitus in 168 000 primary care patients in 63 countries - Balkau, B. (2016)
10.1161/CIRCULATIONAHA.106.676379